An Important Function of Petrosiol E in Inducing the Differentiation of Neuronal Progenitors and in Protecting Them against Oxidative Stress. Issue 10 (5th July 2017) - Liu, Jing; Wang, Linlin; Du, Yuguo; Liu, Sijin
Abstract: Insufficient endogenous neurotrophin supply contributes to neurodegeneration. Meanwhile, neuronal injuries are also attributed to oxidative stress upon toxin exposure. Thus, reconstruction neurite extension and antioxidative stress are the potential strategies for ameliorating neuronal injuries. However, there is no well‐defined therapeutic developed in this regard. In search of such therapeutics, Petrosiol E is identified here as a potent inducer to guide the differentiation of neuronal progenitor cells. Petrosiol E also considerably promotes embryonic stem cell differentiation into neural ectoderm features. Moreover, Petrosiol E reveals an antioxidant function to protect cells from oxidative stress induced by arsenic. Moreover, the molecular mechanism underlying Petrosiol E‐induced neuronal differentiation is uncovered: (a) enhancement of NF‐E2‐related factor 2 (Nrf 2) activity in driving neuronal differentiation; (b) diminishment of oxidative stress. Petrosiol E activates the mitogen‐activated protein kinase and serine/threonine kinase signaling to enhance the activity of Nrf 2. As a result of enhanced Nrf 2 activity, neuronal differentiation is accelerated, and the cellular antioxidation responses are also enforced, even under arsenic‐induced neurotoxicity. Together, the combined results unveil a desirable role of Petrosiol E in driving neuronal differentiation and in combating oxidative stress. This study would open an avenue to develop new therapeutics based on Petrosiol compounds to treat neurodegenerative diseases. Abstract : Petrosiol E facilitates the differentiation of neuronal progenitor cells and also promotes embryonic stem cell differentiation toward neural ectoderm. Mechanistic investigations reveal that Petrosiol E induces neuronal differentiation through: (i) activating Erk and Akt signaling to enhance Nrf2 activity in driving neuronal differentiation; (ii) combating oxidative stress. Petrosiol E manifests these protective effects even under arsenic‐induced neurotoxicity.